The Effect of Profitability, Managerial Ownership and Funding Decisions on the Company Value of PT. Media Nusantara Citra Tbk - Maryanto Maryanto (Cita konsultindo, 2023)
This study aims to determine: 1) Is there an effect of Profitability on Firm Value at PT. Media Nusantara Citra Tbk period 2011-2021? 2) Is there any influence of Managerial Ownership on Company Value at PT. Media Nusantara Citra Tbk period 2011-2021? 3) Is there any influence of the Funding Decision on the Company Value at PT. Media Nusantara Citra Tbk period 2011-2021 ? 4) Is there any influence of Profitability, Managerial Ownership and Funding Decisions on Company Value at PT. Media Nusantara Citra Tbk period 2011-2021? 5) How big is the influence of Profitability, Managerial Ownership and Funding Decisions on Company Value at PT. Media Nusantara Citra Tbk period 2011-2021 ? The research methodology used is descriptive qualitative and descriptive quantitative approaches. The research results are; 1) Partially, there is an influence between profitability on the firm value of PT. Media Nusantara Citra in 2011 – 2021. 2) Partially, there is no influence between managerial ownership on the company value of PT. Media Nusantara Citra, Tbk in 2011 – 2021. 3) Partially, there is no influence between funding decisions on the company value of PT. Media Nusantara Citra Tbk in 2011 – 2021. 4) Simultaneously, there is no influence of profitability, managerial ownership and funding decisions on the company value of PT. Media Nusantara Citra in 2011 – 2021. 5) The magnitude of the influence of profitability, managerial ownership and funding decisions on firm value is 61.5%. While the remaining 38.5%